Neutrosophic $\mathcal{I}$-Statistical Convergence of a Sequence of Neutrosophic Random Variables In Probability - Carlos Granados; Ömer Kişi (Universal Journal of Mathematics and Applications, 2025)
This paper presents a novel perspective on established neutrosophic statistical convergence by utilizing ideals and proposing new ideas. Specifically, we explore the neutrosophic $\mathcal{I}$-statistical convergence of sequences of neutrosophic random variables (briefly, NRVs) in probability, as well as the neutrosophic $\mathcal{I}% $-lacunary statistical convergence and neutrosophic $\mathcal{I}$-$λ $-statistical convergence of such sequences in probability. Additionally, we investigate their interconnections and examine some fundamental properties of these concepts.